Invasion of synanthropic plants into the forest vegetation of the Cedynia Landscape Park (NW Poland) - Stępień, Edyta (Biodiversity: Research and Conservation, 2010)
The distribution of synanthropic plants was studied in the Cedynia Landscape Park (Cedyński Park Krajobrazowy), with particular reference to alien species and their capability to penetrate into forest ecosystems. The research was conducted by the cartogram method in the Atpol system (1-km grid squares). The Park is situated within the Western Pomeranian Province and includes two large woodland complexes: the Piasek Forest (Puszcza Piaskowa) and the Mieszkowice Forest (Lasy Mieszkowickie). The forest vegetation is exposed to various forms of human pressure. Results of this study show that the vascular flora of forests of the Park is composed of 609 species: 506_native taxa (277_non-synanthropic spontaneophytes and 229_apophytes) and 107_anthropophytes (49_archaeophytes, 48_kenophytes, and 9_diaphytes). Most synanthropic plants in the studied forests occur near roads, cottages, and river banks. Contributions of various historical-geographic groups to the total number of species varied between forest types, but apophyte species were usually most numerous. In contrast to some earlier reports, not only alien but also native species were found to be more diverse near forest roads than in the forest interior. Spontaneophytes are equally diverse, while apophytes are much more diverse near roads.